Kiliseden Camiye Dönüştürme ve İstanbul’da Kiliseden Dönüştürülen Camiler Hakkında Notlar - Düzenli, Halil İbrahim (FSM Vakıf Üniversitesi, 2020)
Bir dinin/inancın ibadet ritüellerinin toplu olarak gerçekleştirildiği “kutsal” mekânların başka bir din/inanç ritüelleri için kullanılmaya başlanması, mekânların bu anlamdaki dönüşümleri tarih boyunca karşılaşılan durumlardır. Söz konusu dönüşümlerin coğrafyaya, tarihsel döneme, belli inanç faktörlerine, siyasal iklime, iktidar ilişkilerine vb. göre farklılıklar gösterdiği söylenebilir. Bu makalede bir mesele olarak “kutsal mekânın dönüşümü” ve İstanbul özelinde kiliseden camiye dönüşüm irdelenecektir. Zeyrek Camii (Pantakrator Kilisesi/Manastırı) gibi bazı dönüşümlere ayrıca değinilecektir. İstanbul’daki dönüşümler literatürde farklı sayı ve isimlerde yer almaktadır. Makalede bu literatürün biraraya getirilmesi, bazı tashihler yapılması ve toparlanması amaçlanmaktadır. Bugün İstanbul’da ismi bilinen, halen ayakta veya kaybolmuş olsa da konumları tahmin edilen kırk adet kiliseden çevrilme cami bulunmaktadır. Makalenin temel savı kiliseden camiye dönüştürme eyleminin bütüncül veya tek bir sebebe bağlı olarak açıklanamayacağı, her durumun/tekil örneğin farklılıklar barındırdığıdır. Kiliseler bir gayr-i müslim memleketini fethetmenin sembolü olarak, ilâhi nizamın yeniden tesisi için, demografik yapı değişimlerine bağlı olarak, harap olan yapıların ihtiyaç doğrultusunda yeniden kullanımı gibi nedenlerle camiye çevrilmiştir.

The transformation of “sacred” places where the rituals of worship belonging to one religion/faith are used to be performed collectively in order for the use of rituals belonging to another religious/faith is frequently encountered throughout history. It can be said that these transformations vary according to geography, historical period, certain belief factors, political climate, power relations, and etc. This article will discuss the “transformation of a sacred place” as an issue in general and the transformation of a church into a mosque in Istanbul in particular. Some transformations, such as the Zeyrek Mosque (the Church of the Monastery of Christ Pantokrator), will be discussed separately. Such transformations in Istanbul are cited in different numbers and names in literature. In this article, it is aimed to combine this literature, making some revisions and collecting together. Today, there are forty mosques in Istanbul, which have been converted from churches whose names are known, some of which are still surviving while others are lost but with the predicted locations. The main argument of the article is that the action of transforming from church into mosque cannot be explained solely grounded upon a holistic or single cause, and that each situation/single example contains differences. Churches have been transformed into mosques for reasons such as a symbol of conquering a non-Muslim country, re-establishing the divine order, or re-use of ruined structures due to the needs emerging depending on the demographic changes.
Transforming Churches into Mosques and Notes on Converted Churches in Istanbul
Keywords: Cami; Kilise; Dönüşüm; İstanbul; Zeyrek Cami; Mosque; Converted Church; Transformation; Istanbul; Zeyrek Mosque